Professional Training of Future Teachers of Physical Culture for Animation Leisure Activities - Anton Holenkov (Educational Challenges)
The purpose of the study is to determine the need for professional competencies development for future teachers of physical culture in the field of animation leisure activities, taking into account modern educational requirements and trends.